TDP-43 proteinopathies: a new wave of neurodegenerative diseases. Issue 1 (11th November 2020) - de Boer, Eva Maria Johanna; Orie, Viyanti K; Williams, Timothy; Baker, Mark R; De Oliveira, Hugo M; Polvikoski, Tuomo; Silsby, Matthew; Menon, Parvathi; van den Bos, Mehdi; Halliday, Glenda M; van den Berg, Leonard H; Van Den Bosch, Ludo; et al.
Abstract : Inclusions of pathogenic deposits containing TAR DNA-binding protein 43 (TDP-43) are evident in the brain and spinal cord of patients that present across a spectrum of neurodegenerative diseases. For instance, the majority of patients with sporadic amyotrophic lateral sclerosis (up to 97%) and a substantial proportion of patients with frontotemporal lobar degeneration (~45%) exhibit TDP-43 positive neuronal inclusions, suggesting a role for this protein in disease pathogenesis. In addition, TDP-43 inclusions are evident in familial ALS phenotypes linked to multiple gene mutations including the TDP-43 gene coding ( TARDBP ) and unrelated genes (eg, C9orf72 ). While TDP-43 is an essential RNA/DNA binding protein critical for RNA-related metabolism, determining the pathophysiological mechanisms through which TDP-43 mediates neurodegeneration appears complex, and unravelling these molecular processes seems critical for the development of effective therapies. This review highlights the key physiological functions of the TDP-43 protein, while considering an expanding spectrum of neurodegenerative diseases associated with pathogenic TDP-43 deposition, and dissecting key molecular pathways through which TDP-43 may mediate neurodegeneration.